Barriers to help-seeking in men diagnosed with benign colorectal diseases - Oberoi, D.; Jiwa, Moyez; McManus, Alexandra; Hodder, R. (PNG Publications, 2015)
Objective: To explore the help-seeking pathway for lower bowel symptoms in men diagnosed with benign bowel diseases. Methods: Semi-structured interviews were conducted. The data were analyzed thematically using Andersen's Model of Patient Delay as the theoretical framework. Results: The major delaying factors were attribution of symptoms to self-limiting conditions, failure to make time to visit a GP, low expectation of help from the GP, fear of cancer diagnosis and embarrassment. Conclusion: The major causes of delay in helpseeking were related to the participants, whereas factors associated with treatment delay were less prominent in diagnostic delay.